Shakespeare and Covid Drama in This England (Winterbottom, 2022) - Rasmus, Agnieszka (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
This article considers the significance of different Shakespearean allusions in a political docudrama miniseries This England (2022), directed for Sky by Michael Winterbottom and scripted by Winterbottom and Kieron Quirke. The action focuses on the first crucial months in England after the outbreak of the Covid-19 pandemic, offering a panoramic view of the nation under duress as a newly formed government, with Boris Johnson at its helm, mishandles the crisis. The article seeks to explain the presence of multiple Shakespearean references, from the title alone, through numerous direct quotations to the casting of Kenneth Branagh as Johnson. Shakespearean traces play a pivotal, though confusing, role as they both critique the actions of the government and its leader by offering an ironic framing device while increasing the viewer’s sympathy for its central protagonist via the presence of a Shakespearean celebrity.